Prevalence of Edentulism, Associated Factors, Perceived Treatment Needs and Barriers for Dental Care among the Elderly in a Rural Area of Puducherry, India: A Communitybased Mixed-method Study - Ranjana Ravindranath; Jayalakshmy Ramakrishnan; Vijayageetha Mathavaswami; Vanessa Ravel; Balasubramanian Madhan (Journal of Clinical and Diagnostic Research)
Introduction: Edentulism is a significant cause of poor oral health among the elderly in India. It affects their quality of life, particularly in terms of nutrition, phonetics and aesthetics. Most studies assessing edentulism in India are hospital-based, which may not provide an accurate representation of the general population. Therefore, community-based studies are essential to accurately estimate the prevalence of edentulism and enable the planning of specific strategies to promote oral health. Aim: To estimate the prevalence of partial and complete edentulism, identify the associated factors, assess the treatment needs and evaluate the perceived barriers influencing the treatment needs of the affected population. Materials and Methods: This was a community-based, mixedmethod study conducted in Department of Preventive and Social Medicine, Jawaharlal Institute of Postgraduate Medical Education and Research (JIPMER), Puducherry, India. The study was carried out over six months from May 2017 to October 2017 and included 328 elderly individuals aged 60 years and above. A pretested semi-structured proforma was used to collect data. Quantitative data on the extent of partial and complete edentulism and treatment needs were collected, while perceived barriers to seeking treatment were assessed qualitatively through indepth interviews. Data analysis was performed using Statistical Package for Social Sciences (SPSS) software version 22.0, with a p-value of <0.05 considered statistically significant. Results: The mean age of the participants was 71.4±7.6 years. The overall prevalence of edentulism was found to be 297 (90.5%) (95% CI=86.7%-93.2%). Of these, partial edentulism was found in 253 (13.4%) (95% CI=72.1%-81.4%), while 13.4% (95% CI=10.1%-17.7%) were completely edentulous. Out of the 297 edentate subjects, 65 (22%) participants reported a perceived need for dental treatment, while 232 (78%) did not perceive a need. Similarly, 285 (96%) participants were professionally determined to need dental treatment and 12 (4%) did not require dental treatment. Age, gender and tobacco use had a statistically significant association with edentulism (p-value <0.05). About 227 (76.4%) of the edentate subjects reported difficulty in chewing. The striking findings revealed a low level of denture use among the participants, with only 20 (6.7%) of the 297 edentulous individuals using dentures. The most common perceived barriers to treatment were a lack of awareness regarding oral health, unaffordability and a lack of social support. Conclusion: The study found a high prevalence of edentulism among the elderly, with significant disparities between perceived and actual needs for prosthetic treatment. Only a small proportion of participants use dentures or seek dental care, emphasising the importance of targeted interventions to raise oral health awareness, reduce treatment costs and provide social support. Policymakers should prioritise oral health promotion programs for the elderly in order to bridge these gaps and improve their quality of life.